Populism Against Europe in Social Media: The Eurosceptic Discourse on Twitter in Spain, Italy, France, and United Kingdom During the Campaign of the 2019 European Parliament Election - Alonso-Muñoz, Laura; Casero-Ripollés, Andreu (Frontiers in Communication, 2020)
Since its inception, the European Union has been facing several challenges. The economic and refugee crises, along with the results of the British referendum, have shaped the future of Europe in the past decade. These challenges among others have encouraged the emergence of populist parties, which aim at disrupting the current status quo posing threats to democracy. In this context, the consolidation of digital media has played a key role in the circulation of populist messages to a large number of people. Such messages have questioned the political and legitimacy terms of the European Union, leading to the ideal scenario of Euroscepticism. This article examines the framing and communication strategies used by the European populist actors regarding the European Union and Euroscepticism. The aim is to identify if there are any significant ideological differences. The sample consists of the shared messages (n = 3,667) by the main European populist political parties of Spain, Italy, France, and the United Kingdom during the European Parliament election campaign in 2019. The messages published on the Twitter accounts of Podemos, Vox, the 5 Star Movement, Lega, Rassemblement National, France Insoumise, The Brexit Party, and the UKIP have been analyzed. Results show that two types of Eurosceptic discourse were detected depending on the ideology. The right-wing populists pose a Euroscepticism exclusionary discourse, based on the loss of sovereignty and the distinction of “they” - “us”, excluding the out-groups whereas the left-wing populists present a Euroscepticism inclusive discourse, to maintain the foundational values of Europe, such as equality or solidarity between different people and countries. This research found that Eurosceptic discourse is used in the communicative strategy of populist political parties on Twitter and highlights the importance of the message frame which makes the difference about it.